Escola do corpo: currículo e implicações de gênero e sexualidades na educação de corpos de bailarinos (as) - Pereira, José Rodolfo do Nascimento (2020)
This research has to analyze the ways in which the curriculum (re) produces, regulates and (re) articulates the learning about body, gender and sexuality in a Dance School in the city of João Pessoa (PB). For some decades, subjects such as body, gender and sexuality (s) have gained visibility in the social sphere and in academic discussions, becoming a privileged object of the eyes of educators, scientists from different fields and religious. In this context, tensions on these themes are caught, bringing us, as educators, the need to reflect, dialogue and problematize about these issues. This research is part of the interface between the fields of Cultural Studies in Education, Gender and Sexuality studies in a post-critical perspective. Methodologically, it is registered as qualitative, whose empirical material was produced from: documentary research, participant observation and semi-structured interview and the empirical material was analyzed from the perspective of Cultural Analysis. Studying the implications of gender and sexualities that are inscribed in the bodies of the dancers, was configured in a way of perceiving the possibilities of pedagogical movements that a curriculum can exercise on the lives of the subjects who decide to develop the practice of ballet. The researched school presented itself as a place that uses different mechanisms to discipline and educate the bodies of boys and girls who practice ballet. The curricula with dance, adopted by the teachers of the school of the body, approach and disapprove at all times of the rules demanded by the ballet technique, making at times that they are disciplined according to the rules of this technique and, in others, they risk transgressing them. Some bodies surrender to the educational processes, and others persist, escape and resist.